Age-related decline in goblet cell numbers and mucin content of the human colon: Implications for lower bowel functions in the elderly - Nicholas Baidoo; Gareth J. Sanger (Experimental and Molecular Pathology, 2024)
Background & aims: Older people experience a greater incidence of lower bowel disorders, including constipation. Causes can include factors associated with growing older, such as use of medications or disease, but compounded by degenerative changes within the bowel wall. It has been suggested that the latter is exacerbated by loss of an effective mucosal barrier to luminal contents. In human colon, little is known about the impact of ageing on key components of this barrier, namely the goblet cells and mucin content. Methods: Changes in the number of goblet cells and density of mucin content were investigated in macroscopically normal human ascending (AC; n = 13) and descending (DC; n = 14) colon from elderly (≥ 67 years) and younger adults (60 years and below). Samples were serially sectioned and stained for haematoxylin and eosin to assess tissue morphology, and alcian blue periodic acid Schiff (ABPAS) and MUC-2 antibody to identify goblet cells producing mucins. New procedures in visualization and identification of goblet cells and mucin contents were employed to ensure unbiased counting and densitometric analysis. Results: Compared with the younger adults, the numbers of goblet cells per crypt were significantly lower in the elderly AC (72 ± 1.2 vs 51 ± 0.5) and DC (75 ± 2.6 vs. 54 ± 1.9), although this reduction did not reach statistical significance when assessed per mucosal area (AC: P = 0.068; DC: P = 0.096). In both regions from the elderly, numerous empty vesicles (normally containing mucins) were observed, and some areas of epithelium were devoid of goblet cells. Thus, the density of mucin content per unit mucosal area were significantly reduced with age. Conclusions: Ageing could result in a reduced number of goblet cells and development of degenerative changes in mucin production. Together, these have implications for the mucus barrier function in the colon of elderly individuals.